Computer Safety, Reliability, and Security : 36th International Conference, SAFECOMP 2017, Trento, Italy, September 13-15, 2017, Proceedings /: 36th International Conference, SAFECOMP 2017, Trento, Italy, September 13-15, 2017, Proceedings. (2017) - Unknown
No abstract available